2019
DOI: 10.1177/0016986219838973
|View full text |Cite
|
Sign up to set email alerts
|

From A (Aggression) to V (Victimization): Peer Status and Adjustment Among Academically Gifted Students in Early Adolescence

Abstract: Peer status is an important indicator and predictor of adjustment. While gifted children tend to enjoy favorable peer status, their social functioning during adolescence is less clear. The current study seeks to enhance this understanding by examining both preference- and reputation-based peer status of gifted adolescents. Peer nominations were used to assess the peer status, aggression, victimization, and prosocial leadership of 327 public school seventh graders (44% male; 42% White). School records provided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 63 publications
(88 reference statements)
0
6
1
1
Order By: Relevance
“…We speculate that a shortcoming in interpersonal factors could contribute to a negative self-perception in their social relationships, a feeling of rejection or exclusion, and no social benefit to being intelligent, even if the objective data do not describe this reality (Lee et al, 2012). It could also be speculated that gifted students’ asynchronous development, and characteristics such as greater sensitivity toward social situations, together with more demanding behavior, makes some gifted adolescents more vulnerable and less competent in their online relationships and/or more prone to show passive aggressive behaviors with greater implications and frequency than nonidentified students (Espelage & King, 2018; Peairs et al, 2019). A straightforward explanation for the distinct pattern of associations found for gifted and nonidentified students regarding the role of interpersonal factors explaining cyberbullying would require new, more specific studies devoted to exploring differences in social strategic behaviors used by gifted and nonidentified students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We speculate that a shortcoming in interpersonal factors could contribute to a negative self-perception in their social relationships, a feeling of rejection or exclusion, and no social benefit to being intelligent, even if the objective data do not describe this reality (Lee et al, 2012). It could also be speculated that gifted students’ asynchronous development, and characteristics such as greater sensitivity toward social situations, together with more demanding behavior, makes some gifted adolescents more vulnerable and less competent in their online relationships and/or more prone to show passive aggressive behaviors with greater implications and frequency than nonidentified students (Espelage & King, 2018; Peairs et al, 2019). A straightforward explanation for the distinct pattern of associations found for gifted and nonidentified students regarding the role of interpersonal factors explaining cyberbullying would require new, more specific studies devoted to exploring differences in social strategic behaviors used by gifted and nonidentified students.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on Internet addiction show that excessive use among young people leads to situations of mood changes, loneliness (Muñoz-Rivas et al, 2010 ), depression, low selfesteem, conflicts with parents (Karaer & Akdemir, 2019;Peng et al, 2019;Yen et al, 2009), lower quality social relationships, and fewer adaptive strategies (Li et al, 2019;Milani et al, 2009). Fisoun et al (2012) conducted a study among secondary school students between 14 and 18 years of age, which found a correlation between symptoms of Internet addiction and antisocial behavior.…”
Section: Giftedness and Internet Addictionmentioning
confidence: 99%
“…Επιπλέον, τα χαρισματικά παιδιά που προσπαθούν, αλλά αποτυγχάνουν να ανταποκριθούν στις εξαιρετικά υψηλές προσδοκίες, μπορεί να υποφέρουν από χαμηλή αυτοεκτίμηση, στρες, κατάθλιψη και γενικά να έχουν κακή προσαρμογή στο σχολικό περιβάλλον (McMann & Oliver, ΕΠΙΠΕΔΑ ΣΥΝΑΙΣΘΗΜΑΤΙΚΗΣ ΝΟΗΜΟΣΥΝΗΣ ΣΤΑ ΧΑΡΙΣΜΑΤΙΚΑ ΠΑΙΔΙΑ ΠΑΙΔΑΓΩΓΙΚΟΣ ΛΟΓΟΣ 1/2021 131 1988. Peairs, Putallaz & Costanzo, 2019). Ευρήματα ερευνών που αφορούν στην ανατροφή των παιδιών και εν γένει στην εκπαίδευσή τους έχουν δείξει ότι η οικογένεια διαδραματίζει σημαντικό και θετικό ρόλο στην ανάπτυξη των ταλέντων και των δυνατοτήτων των χαρισματικών παιδιών (π.χ., Bloom, 1985.…”
Section: συναισθηματική νοημοσύνη και χαρισματικότηταunclassified
“…Research suggests gifted students use relational aggression skillfully as a preferred strategy due to their advanced cognitive abilities (Ogurlu, 2015;Peairs et al, 2019;Pelchar & Bain, 2014). Ogurlu investigated the relationship of ostracism and intelligence with middle school gifted students using the Ostracism Experience Scale for Adolescents and the Wechsler Intelligence Scale for Children (Revised Form).…”
Section: Covert Aggression and Gifted Adolescentsmentioning
confidence: 99%